Use of indirect excretory/secretory enzyme-linked immunosorbent assay (ES-ELISA) for the diagnosis of natural Fasciola hepatica infection in eosinophilic and non-eosinophilic cattle from eastern Turkey - Simsek, Sami; Koroglu, Ergon; Utuk, Armagan Erdem; Altay, Kursat (Tubitak Scientific & Technological Research Council Turkey, 2006)
The aim of this study was to investigate fasciolosis in a group of eosinophilic and non-eosinophilic cattle in eastern Turkey. All the cattle were examined for antibodies against F. hepatica by modified indirect excretory/secretory enzyme-linked immunosorbent assay (ES-ELISA). Of the 1200 cattle tested, 164 (13.6%) were found to be eosinophilic by absolute eosinophil counts. Out of the 164 eosinophilic cattle, 121 (73.7%) were found to be positive for fasciolosis by indirect ES-ELISA, while the rate was only 35% among the non-eosinophilic group (P < 0.001). Our data indicate that parasitic infections should be considered an important cause of eosinophilia, particularly in fasciolosis, and the indirect ES-ELISA is useful as a screening test to examine anti-F. hepatica antibodies for the diagnosis of fasciolosis in cattle.
Keywords: Fasciola hepatica; eosinophilia; ES-ELISA; cattle; Turkey